Long-term Impact of Mode of Delivery on Stress Urinary Incontinence and Urgency Urinary Incontinence: A Systematic Review and Meta-analysis - Tahtinen RM; Cartwright R; Tsui JF; Aaltonen RL; Aoki Y; Cardenas JL; El Dib R; Joronen KM; Al Juaid S; Kalantan S; Kochana M; Kopec M; et al. (ELSEVIER SCIENCE BV, 2022)
Context: Stress urinary incontinence (SUI) and urgency urinary incontinence (UUI) are associated with physical and psychological morbidity, and large societal costs. The long-term effects of delivery modes on each kind of incontinence remain uncertain.Objective: To investigate the long-term impact of delivery mode on SUI and UUI.Evidence acquisition: We searched Medline, Scopus, CINAHL, and relevant major conference abstracts up to October 31, 2014, including any observational study with adjusted analyses or any randomized trial addressing the association between delivery mode and SUI or UUI >= 1 yr after delivery. Two reviewers extracted data, including incidence/prevalence of SUI and UUI by delivery modes, and assessed risk of bias.Evidence synthesis: Pooled estimates from 15 eligible studies demonstrated an increased risk of SUI after vaginal delivery versus cesarean section (adjusted odds ratio [aOR]: 1.85; 95% confidence interval [CI], 1.56-2.19; I-2 = 57%; risk difference: 8.2%). Metaregression demonstrated a larger effect of vaginal delivery among younger women (p = 0.005). Four studies suggested no difference in the risk of SUI between spontaneous vaginal and instrumental delivery (aOR: 1.11; 95% CI, 0.84-1.45; I-2 = 50%). Eight studies suggested an elevated risk of UUI after vaginal delivery versus cesarean section (aOR: 1.30; 95% CI, 1.02-1.65; I-2 = 37%; risk difference: 2.6%).Conclusions: Compared with cesarean section, vaginal delivery is associated with an almost twofold increase in the risk of long-term SUI, with an absolute increase of 8%, and an effect that is largest in younger women. There is also an increased risk of UUI, with an absolute increase of approximately 3%.Patient summary: In this systematic review we looked for the long-term effects of childbirth on urinary leakage. We found that vaginal delivery is associated with an almost twofold increase in the risk of developing leakage with exertion, compared with cesarean section, with a smaller effect on leakage in association with urgency. (C) 2016 European Association of Urology. Published by Elsevier B.V.